Krukenberg’s tumor: about 2 cases - Bouyabla, Hind; Taheri, Hafsa; Kouchih Abdelilah; Bellajdel, Ibtissam; Bouabdellaoui, Fatima Zahra; Guerrouj, Imane; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Krukenberg’s tumor is a rare metastatic malignant tumor of the ovary, it represents 1 to 2% of ovarian tumors, the most frequently described primary site is the gastrointestinal tract. It is an aggressive tumor with a poor prognosis. Surgery is the treatment of choice. It consists of removal of the primary gastrointestinal cancer with bilateral adnexectomy, total hysterectomy, locoregional lymphadenectomy and omentectomy when the gastric tumor is discovered secondary to the ovarian lesion. We have collected over a period of 1 year, between April 2021 and May 2022, 2 observations of Krukenberg tumors secondary to digestive neoplasia that were followed in the department of obstetrics and gynecology of the CHU Mohammed VI Oujda. The aim of this article is to make practitioners aware of the difficulties of diagnostic and therapeutic management of this disease in order to improve its poor prognosis. In our observations, the patients certainly complained of digestive signs but it is the gynecological picture made of pelvic pain which was dominant and the main reason for consultation, the two patients were in very bad general state at their admission. The histological study is the only one able to affirm the diagnosis. On the hormonal level, CA-125 is the marker most frequently used by the authors in Krukenberg tumors. This work reconfirms the poor prognosis of Krukenberg’s tumor given its insidious evolution.